Third Party Employment Branding: Human Capital Inflows and Outflows Following “Best Places to Work” Certifications - Dineen, Brian R.; Allen, David G. (Academy of Management Journal, 2016)
“Best Places to Work” (BPTW) and similar competitions are a proliferating form of third party employment branding. Little is known, however, about how single or repeated third party employment branding occurrences relate to key human capital outcomes. Extending signaling theory by considering signal credibility and comparability, we use archival and survey data from 624 BPTW participants in 16 competitions across a three-year period to develop and test hypotheses linking BPTW certifications to collective turnover rates and key informant perceptions of applicant pool quality. We find that certifications are associated with lower turnover rates, and in addition, propose competing crystallization and celebrity hypotheses that model turnover trajectories with repeated certifications, finding diminishing marginal turnover reductions across multiple certifications. We also examine company size and industry job opening moderators, finding that as certifications increase, applicant pool quality is: (1) higher in smaller companies, and (2) higher when job openings are scarcer. Finally, beyond being certified or not, we find supplemental evidence for effects of the specific certification level achieved (e.g., 2nd versus 15th). This investigation advances theory related to collective turnover, applicant pool quality, and employment branding, and is relevant to company decisions about seeking or re-seeking third party certifications.